Simulation of unsteady aerodynamic load for rigid coaxial rotor in forward flight with vortex particle method - Tan, J.; Sun, Y.; Barakos, G.N. (My University, 2017)
Co-axial rotor systems are frequently used for high-speed helicopters. Nevertheless, issues related to rotor-head drag, aerodynamic performance and vibration should also be considered. Simulating the unsteady aerodynamic loads for a rigid coaxial rotor, including the aerodynamic interactions between rotors and rotor blades, is an essential part of analysing their vibration characteristics. In this paper, an unsteady aerodynamic analysis based on the vortex-lattice method is presented. In this method, a reversed flow model on the retreating side of the coaxial rotor is proposed based on the unsteady panel method. To account for reversed flow, shedding a vortex from the leading-edge is used rather than from the trailing-edge. Moreover, vortex-blade aerodynamic interactions are modelled. The model considers the unsteady pressure term induced on a blade by tip vortices of other blades, and thus accounts for the aerodynamic interaction between the rotors and its contribution to the unsteady airloads. Coupling the reversed flow model and the vortex-blade aerodynamic interaction model with a viscous vortex particle method is used to simulate the complex wake of the coaxial rotor, closing the loop in modelling aerodynamic interactions of coaxial rotors. Following this, the unsteady aerodynamic loads on the X2 coaxial rotor are simulated in forward flight, and compared with the results of PRASADUM (Parallelized Rotorcraft Analysis for Simulation And Design, developed at the University of Maryland) and CFD/CSD computations with the OVERFLOW and the CREATE-AV Helios tools. The results of the present method agree with the results of the CFD/CSD method, and compare better than the PRASADUM solutions. Furthermore, the influence of the aerodynamic interaction between the coaxial rotors on the unsteady airloads, frequency, wake structure, induced flow and force distributions are analyzed. Additionally, the results are also compared against computation for a single rotor case, simulated at similar conditions as the coaxial rotor. It is shown that the effect of tip vortex interaction plays a significant role in unsteady airloads of coaxial rotors at low-speeds, while the rotor blade passing effect is obvious strengthened at high-speed.